The Role of Ethanol, Methyltriphenylphosphonium Bromide and Cetyltrimethylammonium Bromide as Directing Agents in Hydrothermal Synthesis of Aluminosilicate Molecular Sieve (ZSM-5) and Its Morphologies (Journal of Sciences, Islamic Republic of Iran)
Zeolite ZSM-5 presents a great source of interest in catalysis because of its shape selective properties. The absence of a relationship between the template size and shape of the structure generated during the synthesis of zeolites is illustrated by the case of ZSM-5. In this study, we have investigated the role of ethanol, methyltriphenylphosphonium bromide (MTPBr) and cetyltrimethylammonium bromide (CTABr) as neutral and cationic templates on aluminosilicate zeolite formation. Ethanol was also successfully used as a low cost template in the synthesis of ZSM-5. Although the XRD pattern of the synthesized zeolites is similar to the ZSM-5 pattern, the SEM results showed that their morphologies are completely different